ANALISIS PENERAPAN FATWA ZAKAT MAJELIS ULAMA INDONESIA PADA LEMBAGA AMIL ZAKAT NASIONAL DOMPET PEDULI UMAT DAARUT TAUHID PRIANGAN TIMUR - wisandani, iwan (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
This study is entitled "Analysis of the Application of the Fatwa of Zakat of the Indonesian Ulema Council at the National Zakat Amil Institute for the Care of the People of Daarut Tauhid East Priangan". In Indonesia, all Islamic Financial Institutions including Sharia Social Institutions in conducting their operations are based on the MUI fatwa.This research is a qualitative research with content analysis and phenomenological methods, with the following activities: The research will be carried out for six months, tracing literature studies and documents related to zakat fiqh, especially zakat issue fatwas issued by the Fatwa Commission and the National Sharia Council of the Indonesian Ulama Council. , then observations and interviews with amillin at the National Amil Zakat Institution, Dompet Peduli Umat Daarut Tauhid East Priangan, to get an overview of the mechanism for managing zakat.The results showed that the DPU DT in carrying out its activities always adheres to the MUI fatwa on the issue of zakat management. Although there are technical matters which are the policies of zakat managers. DPU DT views that the MUI Fatwa is needed to provide certainty in carrying out zakat management activities so that they run well and correctly and succeed for the prosperity of the community.Key Word : Fatwa Zakat, MUI, Daarut Tauhid